International Tourist Demand for Nature-Based Tourism in Costa Rica: Socio-Demographic and Travel Condition Indicators - Villalobos-Céspedes, Daniel (2009)
In Costa Rica, the demand for tourist activities shows a tendency for nature-based tourism. The present research work analyzes the international demand for this type of tourism according to socio-demographic and travel condition variables. The study includes hiking/trekking, visits to volcanoes, observation of flora and fauna, bird watching and canopy. Data are taken from the Costa Rican Tourism Institute (ICT), from the Air Survey (Encuesta Aérea) to non-resident tourists over the age of 18 who left from the Juan Santamaría Airport during the first quarter of 2007. The travelvariables family group, couple and origin, show a potentially favorable influence on demand for most of these activities. The results obtained allow us to outline a strategy to orientate policies and activities of nature-based tourism in Costa Rica.